Influência da modulação cruzada de fase em algoritmos para CAC/RWA dinâmico - Passos Filho, Ubiratan de Souza (2007)
The constraints of Optical Quality of Service (OQoS) in transparent optical networks are herein addressed through empirical cost functions and from an analytical method based on pump-probe model to calculate the impairments caused by Cross-Phase Modulation (XPM). The joint effect of group velocity dispersion (GVD) and nonlinear effects, like Cross-Phase Modulation (XPM) and Self-Phase Modulation (SPM), are considered through extensive numerical simulation in single and multi-span systems. A representative cost function is then found to encompass the physical impairments of a given link utilization (i.e., launched power, wavelength grid, number of active channels, etc). Finally, this link-based approach is used to demonstrate the simplification of the algorithms for Connection Admission Control (CAC) integrated to the algorithm of Routing and Wavelength Assignment (RWA) in dynamic lightpath provisioning with end-to-end optical QoS constraints at admission. The analytical model is used both to assess the approximated solution and to propose a CAC-WA based on on-line computation of XPM interference in networks built with dispersion compensated links. Comparisons with classical physical layer unaware WA are provided in order to show that the OQoS targets can be met with very limited increase in blocking probability